Effects of Primary Kidney Disease Etiology on Renal Osteodystrophy in Pediatric Dialysis Patients. (8th April 2022) - Sirimongkolchaiyakul, Ornatcha; Wesseling‐Perry, Katherine; Gales, Barbara; Markovic, Daniela; Elashoff, David; Ramos, Georgina; Pereira, Renata C; Hanudel, Mark R; Salusky, Isidro B
ABSTRACT: Congenital diseases of the kidney and urinary tract (CAKUT) and glomerulonephritis are the main causes of chronic kidney disease (CKD) in children. Although renal osteodystrophy (ROD) and indices of mineral metabolism have been characterized in dialyzed children, the impact of primary kidney disease on ROD is unknown. We performed a cross‐sectional study of bone biopsies performed in 189 pediatric dialysis patients aged 12.6 ± 5.4 years. Patients were classified into three groups according to primary kidney disease: CAKUT ( n = 82), hereditary ( n = 22), or glomerular disease ( n = 85). Serum concentrations of calcium, phosphate, alkaline phosphatase (ALP), parathyroid hormone (PTH), and 25(OH) vitamin D were measured at the time of biopsy. Fibroblast growth factor 23 (FGF23) levels were measured in a subset of 59 patients. Levels of calcium, phosphate, PTH, and 25(OH) vitamin D were similar across groups. CAKUT patients had higher serum ALP and lower C‐terminal FGF23 levels. Bone turnover and bone volume parameters did not differ across groups. However, osteoid volume (OV/BV), osteoid surface (OS/BS), and osteoid maturation time (OMT) were highest in the CAKUT group and lowest in the hereditary group. Multiple regression analysis revealed that calcium, phosphate, ALP, and PTH were independently associated with OV/BV and osteoid thickness (O.Th). PTH was an independent factor affecting bone formation rate. The relationship between CKD etiology and bone histomorphometric variables was abrogated after adjustment for biochemical parameters in the multivariable models. Overall, bone histology differed according to CKD etiology in the unadjusted analysis; however, this association could not be confirmed independently of biochemical parameters. Although CAKUT patients had a greater mineralization defect with elevated serum ALP levels, longitudinal studies will be needed to elucidate mediation pathways that might be involved in the complex interplay of CKD‐mineral bone disease (MBD). © 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.